Hochleistungsplasmen zur Synthese diamantähnlicher Kohlenstoffschichten. (October 2015) - Bobzin, Kirsten; Brögelmann, Tobias; Bastürk, Serhan; Engels, Martin
<x xml:space="preserve">Abstract</x> HPPMS high‐performance plasmas for the deposition of diamond‐like carbon coatings Diamond‐like carbon (DLC) coatings Diamond‐like carbon (DLC) coatings can be used in many different applications, due to their adjustable properties like hardness as wear reduction. Regarding to the synthesis of these coatings, research is upon the High Power Pulsed/Impulse Magnetron Sputtering (HPPMS/HiPIMS), which in contrast to conventional processes like the Pulsed Laser Deposition (PLD) provides smooth coatings and therefore less postprocessing. Previous to the coating deposition in‐situ plasma analysis can be utilized to identify the process parameters. The aim relevantof this work was to identify process parameters which enable to generate a high amount and energy of carbon ions, which are required to synthesize hard DLC coatings. Regarding to the carbon ionization the promising process parameters mixture and pressure of the process gas as well as the HPPMS pulse parameters were varied. Finally, process parameters for the DLC coating deposition could be derived from these investigations.